2021
DOI: 10.1111/hir.12387
|View full text |Cite
|
Sign up to set email alerts
|

A survey of health information seeking by cancer patients indicates some problems over medical explanations and terminology

Abstract: Background: Cancer patients may experience stress because of insufficient information about their illness, health condition, or treatment, but some may fear what the information reveals.Objective: This study aims to determine health information-seeking behaviour, the attitudes of cancer patients, the barriers they face in seeking health information and their sociodemographic and disease characteristics. Methods: A survey was conducted with 84 cancer patients in Turkey. Descriptive statistics were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 31 However, since most of the active and vocal users who participate in socializing forums have the highest sense of belonging to the online community, 70 there is a risk of a strong echo chamber effect, where the same (low-quality) information is reproduced within a group of like-minded people. 71 Thus, there is a paradoxical situation in OHCs where social support serves as a driver of belongingness and information sharing, 7 , 24 yet socializing forums, where users very often exchange social support, are also places where problematic QISS is exchanged.…”
Section: Discussionmentioning
confidence: 99%
“… 31 However, since most of the active and vocal users who participate in socializing forums have the highest sense of belonging to the online community, 70 there is a risk of a strong echo chamber effect, where the same (low-quality) information is reproduced within a group of like-minded people. 71 Thus, there is a paradoxical situation in OHCs where social support serves as a driver of belongingness and information sharing, 7 , 24 yet socializing forums, where users very often exchange social support, are also places where problematic QISS is exchanged.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, the readability of cancer information on the Internet is too demanding and most of the information does not meet the criteria for readability and understandability by lay population. [10][11][12][13][14] Despite the evidence that the readability levels regarding oncology information for patients are unacceptably high, the readability of newly created materials from professional societies has not improved to an adequate level and there is still room for advancement in all oncology fields, across information providers. 12,13 One of the organizations that aims to improve the quality of health information for the public is Cochrane, whose Database of Systematic Reviews has emerged as one of the most trustworthy sources for the effectiveness of health interventions, due to its high-quality systematic reviews.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that nearly half of the patients with cancer have difficulty understanding information about the treatment for their particular type of cancer 9 . Moreover, the readability of cancer information on the Internet is too demanding and most of the information does not meet the criteria for readability and understandability by lay population 10–14 . Despite the evidence that the readability levels regarding oncology information for patients are unacceptably high, the readability of newly created materials from professional societies has not improved to an adequate level and there is still room for advancement in all oncology fields, across information providers 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Drawing parallels with the studies of Akbolat et al (2023) and Delemere and Maguire (2023), Jiang and Liu (2023) analysed existing datasets focused on cancer‐related health information seeking behaviour. The authors note that the questionnaire data, collected in China in 2012 and 2017, indicate that cancer information seeking is associated with a greater willingness to undertake screening and attend check‐ups.…”
mentioning
confidence: 98%
“…Akbolat et al (2023) undertook a questionnaire survey of 84 patients with cancer in Turkey to examine the barriers they face in seeking health information. Eighty‐six percent of respondents were married, 57% were male and the mean age of the study population was 57 years.…”
mentioning
confidence: 99%